Application of mathematical modelling for assessing the biological half-times of chromium and nickel in field studies. Issue 3 (August 1980) - Tossavainen, A; Nurminen, M; Mutanen, P; Tola, S
Abstract : The biological half-times of urinary chromium and nickel excretion and plasma nickel concentration were calculated for four welders and four electroplaters. A linear one-compartment kinetic model gave estimates of the half-times ranging from 15 to 41 hours for chromium in urine, from 17 to 39 hours for nickel in urine, and from 20 to 34 hours for nickel in plasma. The model allows a precise description to be made of a worker's state of exposure as affected by a varying concentration of the metals in the air.